ANALISIS MITIGASI RISIKO PEMBIAYAAN PRODUK CICIL EMAS DENGAN AKAD MURABAHAH PADA BANK SYARIAH INDONESIA KCP MAGELANG SUDIRMAN - Anisah, Rizka Luthvia; Rokhaniyah, Siti (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
The risk mitigation analysis in financing gold installment products with murabahah contracts at Bank Syariah Indonesia (BSI) KCP Magelang Sudirman focuses on the application of the 5C principle. Gold installment financing is one of BSI's products with the intention of helping customers to minimize rupiah inflation. Gold installments have investment opportunities that look attractive and easy, but they are also risky businesses and need to be managed very well. Risks that arise along with the growth of the banking sector can have a negative impact on the company. The main purpose of this article is to identify the existing risks and mitigation strategies implemented by BSI KCP Magelang Sudirman. The research approach used is qualitative analysis through interviews, observations, documentation and document review processes. The results of the study show that the risks faced include credit risk (related to the character and capacity of customers), market risk (related to the gold market), and operational risk (caused by human error). BSI KCP Magelang Sudirman implements mitigation strategies such as conducting a thorough assessment of customers before providing financing, to find out the character and capacity of customers, evaluate the value of collateral, and monitor market prices.